Predictors of personal polycyclic aromatic hydrocarbon exposures among pregnant minority women in New York City. - Tonne, Cathryn C (2004)
As part of a multiyear birth-cohort study examining the roles of pre- and postnatal environmental exposures on developmental deficits and asthma among children, we measured personal exposures to polycyclic aromatic hydrocarbons (PAHs) among 348 pregnant women in northern Manhattan and the South Bronx, New York. Nonsmoking African-American or Dominican women were identified and recruited into the study. During the third trimester of pregnancy, each subject wore a personal air monitor for 48 hr to determine exposure levels to nine PAH compounds. In this study, we examined levels of exposures to PAHs and tested for associations with potential predictor variables collected from questionnaires addressing socioeconomic factors and day-to-day activities during pregnancy as well as activities and environmental exposures during the 48-hr monitoring period. Reliable personal monitoring data for women who did not smoke during the monitoring period were available for 344 of 348 subjects. Mean PAH concentrations ranged from 0.06 ng/m3 for dibenz[a,h]anthracene to 4.1 ng/m3 for pyrene; mean benzo[a]pyrene concentration was 0.50 ng/m3. As found in previous studies, concentrations of most PAHs were higher in winter than in summer. Multiple linear regression analysis revealed associations between personal PAH exposures and several questionnaire variables, including time spent outdoors, residential heating, and indoor burning of incense. This is the largest study to date characterizing personal exposures to PAHs, a ubiquitous class of carcinogenic air contaminants in urban environments, and is unique in its focus on pregnant minority women.